Were the Enabling Conditions for Sino-US Rapprochement Unique or Could Better Relations Today be Built on Similar Conditions and Foundations? - Shen, Dianchen (Transactions on Social Science, Education and Humanities Research, 2024)
The relationship between the United States and China has been a topic of great interest and concern for many decades. The history of US-China relations is marked by periods of both cooperation and conflict. A decisive moment in this transformation occurred at the end of 1978 with the normalisation of diplomatic relations with the People’s Republic of China (PRC). Ping-Pong diplomacy was a stunning success that not only paved the way for Nixon’s trip but also caused a sensation around the world (CCP Politburo’s report on the US-China summit, 1971). However, in recent years, tensions between the two countries have risen significantly. Just as Nixon predicted during this low moment, his biographer, Richard Reeves, recounted how Nixon told him that the interests between China and the U.S. were fundamentally different over the long term and the clash between them "was inevitable" (Nixon, 1978). This essay takes the position that the conditions for rapprochement are unique and that building a stronger US-China relationship cannot be achieved by relying on similar conditions and foundations as those that enabled rapprochement in the 1970s.